Nilai Pendidikan Karakter dalam Novel Perempuan Berkalung Sorban Karya Abidah El Khalieqy sebagai Bahan Ajar Pembelajaran Sastra di Kelas XII Sekolah Menengah Atas (SMA) - -, Tri Budi Astuti (Educreative : Jurnal Pendidikan Kreativitas Anak, 2021)
This study aims to describe: (1) the value of character education in the novel Perempuan Berkalung Sorban (2) the novel as a teaching material for literature learning in class XII SMA. This research is a qualitative descriptive study. The data source in this study is a document in the form of the novel Perempuan Berkalung Sorban by Abidah El Khalieqy. The data collection of this research includes reading, recording, and analyzing documents. The data analysis technique used in this study is a content analysis technique which includes data reduction, data presentation, and data inference. The results of this study (1) the value of character education that appears in the novel Perempuan Berkalung Sorban is religious, hard work, democratic, curiosity, fond of reading, and social care (2) the novel Perempuan Berkalung Sorban can be used as teaching material for learning literature in the classroom. XII SMA with basic competency in analyzing the contents and language of the novel.